IDENTIFIKASI STANDAR KOMPETENSI AHLI TEKNIK BANGUNAN DI INDONESIA - Rahman, Muhammad Haristo (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2023)
In order to build a building that meets the requirements for reliability, comfort, economy, and according to the planned age, a building expert is needed who has competence in designing, implementing, and supervising the structure of the building being built. So this research was conducted with the aim of knowing the elements and job competencies of building engineers in SKKNI Number 192 of 2016 as indicators of job descriptions and mastery of scientific disciplines and knowledge and skills in building engineering work situations. This study used a descriptive qualitative approach with a content analysis research design by analyzing the competency elements of SKKNI Building Engineers. From the research results, the main objective of the building engineer's competency content is the ability to build buildings that meet the requirements of reliability, comfort, economy, and according to the planned age, it requires a building expert who has competence in designing, implementing, and supervising the structure of the building being built. After identifying the structure of the competency units contained in the SKKNI of Building Engineering Experts, it is known that there are 28 (twenty eight) competency unit titles.